Dual-enzymatically crosslinked hyaluronic acid hydrogel as a long-time 3D stem cell culture system. (11th June 2020) - Gao, Feng; Li, Jinrui; Wang, Luyu; Zhang, Dan; Zhang, Junni; Guan, Fangxia; Yao, Minghao
Abstract: Stem cell-based tissue engineering shows enormous potential for regenerative medicine. Three-dimensional (3D) stem cell culture is the most basic aspect of tissue engineering. However, achievement of a perfect scaffold for highly efficient 3D cell culture is currently still limited. Herein, a new hyaluronic acid hydrogel dual-enzymatically crosslinked by horseradish peroxidase and choline oxidase is developed as a 3D stem cell culture system. This hydrogel possesses superior stability over two months, controllable biodegradability with hyaluronidases, a high swelling ratio exceeding 6000%, and excellent cytocompatibility in vitro and biocompatibility in vivo . More importantly, a long-time and highly cellular activity 3D culture of bone marrow-derived mesenchymal stem cells was achieved in vitro over 20 days. All these encouraging results highlight the great potential of this new hydrogel for 3D culture and tissue engineering.